HYPODERMOCLYSIS IN ONCOLOGY PATIENTS RECEIVING PALLIATIVE CARE - Eveline Treméa Justino; Fernanda Spiel Tuoto; Luciana Puchalski Kalinke; Maria Fátima Mantovani (Universidade Federal do Paraná, 2013)
This descriptive, quantitative and prospective study aimed to describe the experience of the use of hypodermoclysis in patients receiving palliative care and treatment for pain, in a hospital which is a center of excellence in oncology, in the state of Parana. 16 participants were monitored from November 2008 through to September 2009; data collection was undertaken using a structured instrument and monitoring took place up until the use of hypodermoclysis was interrupted. The proportion of use of hypodermoclysis among the patients was 0.02%, and was carried out most commonly in the outpatient center of this speciality. The principal indication was the advanced stage of the disease (56.25%) and the drug most used was morphine (93.75%), and hypodermoclysis was used in 31.25% of the patients as a route of hydration. The use of this alternative route for administering fluids in palliative care in the hospital in question is low, and the adoption of a standard protocol and its dissemination could contribute to its use.